The didacticization of labor writing in the teacher training: course didactic sequence, learning through reviews - Gomes, Renilson Nóbrega; Silva, Williany Miranda da (Revista Letras Raras, 2023)
Mastery of a genre is a condition for employing it in the realization of a discourse project (BAKHTIN, 2003). However, in a school context, we still see a meaningless and lighthearted teaching approach, lacking a more systematic work as it provides a didactic sequence (SWIDERSKI; COSTA-HÜBES, 2009). In this direction, in this article, we reflect on teacher training from the didactic treatment given to the didactic sequence. Thus, we aimed to: 1st) to identify processes of didacticization of labor writing in the Didactic Sequence course: learning through reviews and 2nd) to analyze perspectives of teacher training that are refracted in the didacticization of the didactic sequence. For that, we consider theoretical notions about labor writing, didactic sequence and traditional paradigms and complexity in education. As for the methodology, it is a qualitative research of the documental analysis type, in whose data generation, we used a teaching plan. The results indicate that the didacticization of the didactic sequence is effective with a focus on teaching and the production of a review and not on the teaching device in question, as expected in a teacher training course, associating theory with the practice of the student.